Lo esencial es invisible a los ojos - Sosa, Edgardo Rodolfo (Buenos Aires Paulinas, 1997)
<Saint Exupery, Antoine de>
<Reflexiones> a partir del <Principito>
Keywords: ETICA; ANALISIS LITERARIO; EDUCACION EN VALORES; CONCEPTOS MORALES